BN information chiefs play pivotal roles - New Sabah Times English, (KK) (New Straits Times, 2013)

(untitled)
As he carefully realigned his side-parted hairstyle before meeting journalists for interviews,Datuk Ahmad Maslan would often straighten his shirt's crisp collars with the tips of his fingers.